Maternally transferred dioxin‐like compounds can affect the reproductive success of European eel. (3rd December 2015) - Foekema, Edwin M.; Kotterman, Michiel; de Vries, Pepijn; Murk, Albertinka J.
Abstract: Reported concentrations of dioxin‐like compounds accumulated in the European eel ( Anguilla anguilla ) were used to perform a risk assessment for eel larval survival, taking into account a modeled amplification of tissue concentrations with a factor of 1.33 during spawning migration. The calculated concentrations of dioxin‐like compounds finally deposited in the eggs were compared with the internal effect concentrations for survival of early life stages of the European eel; these concentrations, by lack of experimental data, were estimated from a sensitivity distribution based on literature data by assuming that eel larvae are among the 10% most sensitive teleost fish species. Given concentrations of dioxin‐like contaminants and assuming a relatively high sensitivity, it can be expected that larvae from eggs produced by eel from highly contaminated locations in Europe will experience increased mortality as a result of maternally transferred dioxin‐like contaminants. As historical persistent organic pollutant concentrations in eel tissue were higher, this impact must have been stronger in the past. Potential effects of other compounds or effects on the migration, condition, and fertility of the parental animals were not taken into account. It is important to further study the overall impact of contaminants on the reproductive success of the European eel as this may have been underestimated until now. Environ Toxicol Chem 2016;35:241–246. © 2015 SETAC